Epidemiology of Suicidal Behavior in Malaga (Spain): An Approach From the Prehospital Emergency Service - Moreno-Küstner, Berta; del Campo-Ávila, José; Ruíz-Ibáñez, Ana; Martínez-García, Ana I.; Castro-Zamudio, Serafina; Ramos-Jiménez, Gonzalo; Guzmán-Parra, José (Frontiers in Psychiatry, 2019)
Objective: This study aims to analyse the characteristics of the calls made to the Málaga Prehospital Emergency Service (PES) for suicidal behaviour based on their sociodemographic, temporal and care variables. Method: This is a retrospective, descriptive study that records all the calls made to the SUE due to suicidal behaviour (suicide attempts and consummated suicides) in 2014. Sociodemographic variables (age, sex and health district) and variables related to the calls (time-slot, time of day, type of day, month, quarters and season of the year, time of the year, holiday period, priority and number of resources mobilised) were extracted from these calls. The number of cases and percentages were presented for the qualitative variables. The rates per 100,000 were calculated by sex and health district and presented with the corresponding 95% confidence interval (CI). Results: Of the total valid calls (n=181,824), 1,728 calls were made due to suicidal behaviour (0.9%). The mean age was 43.21 (±18) years, and 57.4% were women. The rate of calls due to suicidal behaviour was 112.1 per 100,000 inhabitants. The health district of Málaga (city) yielded the highest rate (121.7 per 100,000 inhabitants), whereas Ronda yielded the lowest (94.62 per 100,000 inhabitants). Conclusions: Prevention plans adapted to the reality of care system by specific study areas can be drawn up based on the variability found in the rate of calls made to the prehospital emergency service due to suicidal behaviour.